Ok lá þar at óvilja hennar: A Reconsideration of Sexual Violence in the Old Norse World. (January 2023) - Bell, Jacob
Despite the popularized image of the raping and pillaging Viking warrior, the culture of sexual violence in Old Norse society has remained surprisingly understudied. This article uses skaldic verses, a literary genre produced in Iceland and Norway, mainly from the ninth through the fourteenth centuries, to suggest a reconsideration of sexual violence in the Old Norse world. It suggests that skaldic verses can help scholars discern a spatial and cultural geography of sexual violence against free men, women, and slaves, which suggests it was widespread and multidimensional and had ties to a pan-north Atlantic slave trade in the Viking Age.